2014
DOI: 10.18632/oncotarget.2646
|View full text |Cite
|
Sign up to set email alerts
|

End-binding 1 protein overexpression correlates with glioblastoma progression and sensitizes toVinca-alkaloidsin vitroandin vivo

Abstract: End-binding 1 protein (EB1) is a key player in the regulation of microtubule (MT) dynamics. Here, we investigated the role of EB1 in glioblastoma (GBM) tumor progression and its potential predictive role for response to Vinca-alkaloid chemotherapy. Immunohistological analysis of the 109 human GBM cases revealed that EB1 overexpression correlated with poor outcome including progression-free survival and overall survival. Downregulation of EB1 by shRNA inhibited cell migration and proliferation in vitro. Convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 46 publications
6
45
0
Order By: Relevance
“…Furthermore, EB1 overexpression correlated with glioblastoma progression and migratory potential, whereas downregulation of EB1 by shRNA inhibited cell migration and proliferation in vitro [52]. Modulation of γ-actin expression leads to similar functional changes in normal [53] and neoplastic cells [23, 27, 54].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EB1 overexpression correlated with glioblastoma progression and migratory potential, whereas downregulation of EB1 by shRNA inhibited cell migration and proliferation in vitro [52]. Modulation of γ-actin expression leads to similar functional changes in normal [53] and neoplastic cells [23, 27, 54].…”
Section: Discussionmentioning
confidence: 99%
“…(phase IIA) or oral (phase I) administration (18)(19)(20). Previously, we reported that microtubule þ End-binding 1-protein (EB1) was a factor of bad prognosis in glioblastoma, and that Vinca-alkaloid chemotherapy could improve the treatment of glioblastoma patients with an EB1-overexpressing tumor (21). We demonstrated notably the EB1-dependent migratory potential of two human primary glioblastoma CSLCs, GBM6 and GBM9, established from sorted A2B5 þ cells (22).…”
Section: Introductionmentioning
confidence: 90%
“…ShRNA plasmid that specifically knocked out human EB1 (NM_012325) and negative shRNA control plasmid (Mission non-target shRNA control vector) were obtained from Sigma-Aldrich. Cells were transfected according to the protocol previously described (21). Stable GFP-shRNA-transfected cells were obtained after transfection with peGFP-N3 vector (Clontech) using lipofectamineTM 2000 system (Invitrogen) and selection with 0.6 mg/mL geneticin (Life Technologies).…”
Section: Cell Transfectionsmentioning
confidence: 99%
“…Several studies reported their localization in TM membrane (32,33), especially for MMP-2 and MT1-MMP.Our interest arises from the analysis of the role of TMs in tumor progression and of the effect of different drugs on their structures and dynamics (34,35). The inhibition of TMs leads to a decrease in cell migration and proliferation, with obvious consequences on GB treatment (34)(35)(36). The process of growth and retraction of TMs plays a fundamental role for cell-to-cell communication routing (17,18,(20)(21)(22)(23), as well as a transient binding platform for essential proteins that regulate tumor dynamics (37).…”
mentioning
confidence: 99%
“…The process of growth and retraction of TMs plays a fundamental role for cell-to-cell communication routing (17,18,(20)(21)(22)(23), as well as a transient binding platform for essential proteins that regulate tumor dynamics (37). Among these proteins, the presence of microtubule plus end-binding protein EB1 correlates with GB progression and poor survival (36,38). This has led to a great interest in the development of drugs aimed at affecting end-binding proteins expression and, consequently, TM dynamics (35).…”
mentioning
confidence: 99%